2016
DOI: 10.1007/s00044-016-1713-9
|View full text |Cite
|
Sign up to set email alerts
|

New acetylenic derivatives of betulin and betulone, synthesis and cytotoxic activity

Abstract: Betulin 1 and its semisynthetic derivatives exhibit a cytotoxic activity toward various cancer cell lines. These compounds are a promising and potential anticancer candidates. A series of betulin derivatives was prepared and tested for the antiproliferative activity in vitro against T47D breast cancer, CCRF/CEM leukemia, HL-60 promyelocytic leukemia, SW707 colorectal, murine P388 leukemia, as well as BALB3T3 normal fibroblasts cell lines. Cisplatin and betulin 1 were used as a reference compounds. Some derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 23 publications
3
42
0
1
Order By: Relevance
“…Tang JJ et al, identified a small-molecule inhibitor of SREBP, betulin, by compound screening, where SREBP is a major transcription factor that controls the biosynthesis of cholesterol, fatty acid, and triglyceride [114]. Betulin inhibits SREBP by binding SCAP and making the interaction between SCAP and Insig easier, which leads to the ER-retention of SREBP.…”
Section: Anti-hyperlipidaemic Activitymentioning
confidence: 99%
“…Tang JJ et al, identified a small-molecule inhibitor of SREBP, betulin, by compound screening, where SREBP is a major transcription factor that controls the biosynthesis of cholesterol, fatty acid, and triglyceride [114]. Betulin inhibits SREBP by binding SCAP and making the interaction between SCAP and Insig easier, which leads to the ER-retention of SREBP.…”
Section: Anti-hyperlipidaemic Activitymentioning
confidence: 99%
“…The 3-oxo derivative of betulin betulone and its derivatives, exhibiting antitumor, antiinflammatory, aniparasitic, and anti-HIV properties, also demonstrate in vitro cytotoxic activity against different cancer cell lines. [10][11][12][13][14][15][16][17][18][19][20][21][22] Recent studies indicate a clear demand for betulone as a building block for creating effective anticancer agents with minimal side effects. [20][21][22] Currently, the main method of synthesis of betulin oxoderivatives is its oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[10-14] Pyrazole derivatives have been reported as antimicrobial agents in a number of publications,[15-17] but as anti- Acinetobacter, they are unknown. In our efforts to get potent antimicrobial agents,[18] we have synthesized several pyrazole-derived terphenyl like novel molecules. We have found pyrazole-derived N-aryl amines as anti-methicillin resistant Staphylococcus aureus (anti-MRSA) agents.…”
mentioning
confidence: 99%
“…[18] Aromatic amine derivatives are an integral part of many potent antimicrobial agents. [19] All these novel molecules are characterized by 1 H and 13 C NMR spectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation